2017
DOI: 10.7824/rbh.v16i4.562
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de associações e doses de herbicidas em pós emergência do trigo

Abstract: Resumo -As principais plantas daninhas encontradas na cultura do trigo são o nabo e o azevém, e seu controle em pós-emergência é baseado em herbicidas inibidores da enzima acetolactato sintase (ALS) e acetil coenzima A carboxilase (ACCase) que, em função da resistência, limita as opções de controle. Associações de herbicidas têm sido utilizadas em pós-emergência do trigo, porém, seus efeitos na cultura são pouco conhecidos. O objetivo deste trabalho foi avaliar a seletividade de associações de herbicidas e dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 15 publications
3
11
0
15
Order By: Relevance
“…When comparing the application between crop development stages for each treatment, it was found that the tillering stage and after the first node for 2,4-D amine and the first node stage for 2,4-D choline demonstrate the highest barley grain yields. The 2,4-D amine was reported to not affect grain yields of wheat (Piasecki et al, 2017) and barley (Karpinski et al, 2018), which corroborates in parts with what was observed in this work.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…When comparing the application between crop development stages for each treatment, it was found that the tillering stage and after the first node for 2,4-D amine and the first node stage for 2,4-D choline demonstrate the highest barley grain yields. The 2,4-D amine was reported to not affect grain yields of wheat (Piasecki et al, 2017) and barley (Karpinski et al, 2018), which corroborates in parts with what was observed in this work.…”
Section: Resultssupporting
confidence: 92%
“…Post-emergence application of the herbicide 2,4-D amine for barley weed management has caused phytotoxicity of less than 5% in barley plants (Vargas & Roman, 2005) and 10% in wheat crop (Piasecki et al, 2017). These studies corroborate in part with the results found in the present work.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, in the South of Brazil, the herbicides used in the post-emergence of wheat predominantly belong to ACCase and ALS inhibitors (MICHELON et al 2021). Therefore, the most recommended for weed control in wheat and available in larger quantities are the ALS inhibitors (PIASECKI et al 2017). However, these herbicides are the ones that have shown many cases of resistant weeds in recent years (HEAP 2021), and in some countries, the concern lies in the time required for chemical control to show an effect on infective species in wheat crops (WALSH 2019).…”
Section: Introductionmentioning
confidence: 99%